The post-flood impacts on farmers, agricultural sector and food security in Kelantan - Z., Hazran; Man, Norsida; Kamarulzaman, Nitty Hirawaty; Mohd Nawi, Nolila (Human Resource Management Academic Research Society, 2017)
Similar to other countries across the globe, Malaysia experiences climate change and this phenomenon has caused natural disasters such as flood. The objective of this paper is to analyse the perception level toward the impacts of flood on the farming community. A total of 371 farmers in Kelantan who were victims of the flood disaster in 2014 were selected as respondents. The findings confirmed that majority of the respondents (42.9%) had individually suffered losses worth RM 4,001 or more because of the disaster. The flood had negatively affected the flood victims as most of them were low income earners. Majority of the respondents would need two to five months to recover emotionally and psychologically, that is, the same duration needed to resume their normal farming activities.